Utilization of Gracilaria sp. liquid for bioethanol production - Nur Zatul ‘Iffah, Zakaria
Seaweed liquid from filter-pressed drying process of Gracilaria sp. has caused unpleasant odour to the environment. Although this liquid can partially be used as biofertilizer and heavy metals adsorbent, a bigger portion of the liquid remain unutilized thus causing problem to environment. The present study was aimed at utilizing Gracilaria sp. liquid either as ethanol feedstock or supplement in fermentation media. To achieve this aim, Saccharomyces cerevisiae was used as a benchmark. Some locally isolated strains have been screened, isolated and tested their efficacy in fermenting Gracilaria sp. liquid to produce ethanol. Prior to fermentation, the liquid was pretreated using thermal dilute sulphuric acid hydrolysis in sequence to increase reducing sugar concentration and its conditions were statistically optimized by using Response Surface Methodology (RSM) method. The optimum condition of thermal dilute acid hydrolysis obtained was 0.3 M sulphuric acid, 0.7 g/ml of substrate and 120 oC. Nevertheless, all the potential strains isolated in this study produced lower yield as compared to S.cerevisiae. Therefore, this yeast was used in subsequent experiments. However, when used as a supplement in the fermentation media to produce ethanol using S.cerevisiae, the liquid was able to boost the ethanol production three folds from 200 mg/L of 2 % glucose alone to 600 mg/L of 2% glucose in the liquid. Additionally, the Gracilaria sp. liquid was able to substitute yeast extract and peptone within Yeast Potato Dextrose (YPD) media to produce 647.48 mg/l ethanol as compared to only 542.39 mg/l with normal YPD which contains yeast extract and peptone. For that reason, utilization of Gracilaria sp. liquid as the supplement in the medium should be considered because it is capable to enhance ethanol production without addition of other nutrients.